New developments in force fields for biomolecular simulations. (April 2018) - Nerenberg, Paul S; Head-Gordon, Teresa
Highlights: Biomolecular force fields (FFs) have progressed rapidly in the past five years. Fixed-charge FF accuracy has improved, but challenges remain for complex systems. Early studies using polarizable FFs for complex systems show their promise. New FF paradigms and parameterization methods are emerging. Abstract : Biomolecular force field development has been instrumental in improving the predictive power of molecular simulations over the past four decades. More recently, the era of large quantitative experimental datasets and ubiquitous high performance computing power has enabled rapid progress in the field. In this review we summarize recent developments in all-atom protein, nucleic acid, and small molecule force fields, paying specific attention to developments in parameterization methods and improvements in the representations of nonbonded interactions that are critical for solving the challenging biophysical problems of the present. We also sketch out new avenues for force field development and grand challenge applications for the near future.